MANAJEMEN KINERJA KELOMPOK USAHA PRODUKSI WINGKO SINGKONG (WINGSING) DI KELURAHAN KANDRI SEMARANG - Murdani, Murdani; Hadromi, Hadromi (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2016)
Cassava Wingko (Wingsing) is a traditional Indonesian food. Wingko is a kind of cake made from cassava, coconut and other ingredients. Wingsing has an important role for economic growth in the Kandrivillage. More foreign tourists are coming to the village Kandri which is a gateway to travel in wadung Jatibarang as wadug Jatibarang in villages Kandri were officially opened. The purpose of this activity was to: improve the quality and capacity of the Wingsing products through improving the production and the management aspects of the industry partners. The outcomes of this activity were; (1) increased understanding of the partner about management concepts and hygienicproduction techniques of Wingsing. (2) marketable Wingsing packaging techniques, (3) writing in national journals, or an accredited journal, or an international journal about Wingsing productionin the village Kandri. The methods used in the IbM consisted of (1) observation to identify the the problems faced bythe Wingsing producers, (2) a discussion meeting with the Wingsing producers to agree on the techniques to overcome the problems, (3) counseling of hygienictechniques of Wingsing production, (6) integrated training and assistance to improve the quality and quantity of products, marketableWingsingpackaging techniques, improved marketing system of Wingsing. The results of this activity indicated an improvement quality and quantity of Wingsing production, which included the results of a more marketable packaging design, understanding about more hygienicWingsing production process. The indirect impact of this activity was on the increase of production and revenue of Wingsing small business venture. Furthermore, the results of activities has been written in an article and have been sent to International Journal of Research in Higher Education published by Sciedu Press in Canada.